1992
DOI: 10.1007/bf00219515
|View full text |Cite
|
Sign up to set email alerts
|

Volume-dependent regulation of sodium and potassium fluxes in cultured vascular smooth muscle cells: Dependence on medium osmolality and regulation by signalling systems

Abstract: To identify ion transport systems involved in the maintenance of vascular smooth muscle cell volume the effects of incubation medium osmolality and ion transport inhibitors on the volume and 86Rb and 22Na transport in cultured smooth muscle cells from rat aorta (VSMC) have been studied. A decrease of medium osmolality from 605 to 180 mosm increased intracellular water volume from 0.6 to 1.3 microliters per 10(6) cells. Under isosmotic conditions, cell volume was decreased by ouabain (by 10%, P less than 0.005)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

1993
1993
2007
2007

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 40 publications
0
16
0
Order By: Relevance
“…2a, curve 3). These results suggest that suppression of bumetanide-resistant K + influx in hyperosmotic medium is caused by the inhibition of KCC reciprocally regulated by cell volume and detected in our previous studies [6,43].…”
Section: Nkcc Activitymentioning
confidence: 72%
See 1 more Smart Citation
“…2a, curve 3). These results suggest that suppression of bumetanide-resistant K + influx in hyperosmotic medium is caused by the inhibition of KCC reciprocally regulated by cell volume and detected in our previous studies [6,43].…”
Section: Nkcc Activitymentioning
confidence: 72%
“…In Cl − -free PSS, KCl, NaCl and MgCl 2 were substituted with Na-gluconate, K-gluconate and MgSO 4 , respectively, whereas CaCl 2 was omitted. Previously, it was shown that the o does not affect volume-dependent regulation of ouabain-resistant 86 Rb fluxes in VSMC [43]. Chemicals were obtained from Sigma (St. Louis, Mo., USA) with the exception of EGTA, POPOP, PPO (Serva, Heidelberg, Germany), verapamil (Orion, Helsinki, Finland) and cell culture medium (Gibco BRL, Gaithersburg, Mo., USA).…”
Section: Cultured Vsmcmentioning
confidence: 99%
“…Incubation was terminated by SDS/EDTA mixture. The cell lysates were applied to a column containing 0.5 g DOWEX-AG 1-X8 (formate form), and IP 3 was resolved as described elsewhere (Orlov et al, 1992).…”
Section: Inositol Triphosphate Productionmentioning
confidence: 99%
“…It has been shown that both Na-K-Cl cotransport [8,9] and Na/H exchange [8] are activated under hypertonic shrinkage of VSMC, whereas the RVI of isosmotically-shrunken VSMC is mediated exclusively by Na-K-Cl cotransport [10]. Both K + influx and efflux have been observed in hyposmotically-swollen VSMC treated with inhibitors of the Na/K pump and Na-K-Cl cotransport [8], suggesting activation of the K-Cl cotransporter and/or K + and Cl -channels, leading to the generation of net K + efflux due to the outwardly directed electrochemical gradient of these ions. The aim of this study was to identify the relative contributions of these ion transporters in swelling-induced K + fluxes in VSMC.…”
Section: Introductionmentioning
confidence: 99%